Design of byzantine fault-tolerant transaction commit protocol for heterogeneous distributed databases. (1st January 2014) - Ramesh, Dharavath; Kumar, Chiranjeev
In this paper, we present a byzantine transaction commit protocol-based recovery algorithm for distributed database environment. As two-phase commit protocol is restricted due to its blocking nature, it is enhanced to cope with the byzantine coordinator. The proposed protocol can tolerate the fault occurrences to make the transactions complete and takes utmost care towards atomic commit. We also analyse the methodology between different site transactions by analytical performance to make the protocol sufficient. We also perform extensive simulations for choosing better throughput and latency.